A Framework for Transforming Indian Sports Goods Manufacturing Industry. (December 2021) - Kumar, Shailendra; Suhaib, Mohd; Asjad, Mohammad
The Indian manufacturing industry is gradually adopting the sustainable productivity-oriented processes of the fourth industrial revolution (4IR), but the sports goods manufacturing (SGM) sector has lagged far behind. In India, the city of Meerut is one of the hubs of SGM, providing about 25, 000 direct jobs and exporting goods worth around ₹4.86 billion (~US$75 million). The thousands of mini, micro and small household manufacturing units of the Meerut sports goods manufacturing (MSGM) cluster widely operate with the centuries-old labour-intensive manufacturing practices. MSGM cluster has a vast untapped potential to increase productivity, quality and sustainability of processes. To remain relevant in this competitive era, a transformation of the sports goods manufacturing industry (SGMI) is the need of the hour. For this, the requirement for an integrated transformational framework capable of transforming the processes of the manufacturing cluster from its current state to intelligent manufacturing is felt. It will help the SGMI sustain and uplift its workforce's employability, income and living standards. This transformation also invites the other allied industries to operate in the cluster, generating employment and business opportunities. In Decision-Making Trial and Evaluation Laboratory (DEMATEL)-based analysis of the MSGM cluster, cause–effect relations among eleven prevalent transformational challenges are deduced. From both prominence ranking and cause–effect relations for the eleven prevalent transformational challenges, 'management's willingness', 'government support system', and 'awareness and clear understanding of benefits (ROI)' are observed among the prominent factors to be overcome. A transformational framework for SGMI from its present state to the I4.0 state is proposed. The study and proposed scalable framework with causal relationships will serve as a road map and tool for the smooth and effective transformation of the SGMI cluster.